2003
DOI: 10.1051/gse:2003014
|View full text |Cite
|
Sign up to set email alerts
|

Application of disease-associated differentially expressed genes – Mining for functional candidate genes for mastitis resistance in cattle

Abstract: -In this study the mRNA differential display method was applied to identify mastitisassociated expressed DNA sequences based on different expression patterns in mammary gland samples of non-infected and infected udder quarters of a cow. In total, 704 different cDNA bands were displayed in both udder samples. Five hundred-and-thirty two bands, (75.6%) were differentially displayed. Ninety prominent cDNA bands were isolated, re-amplified, cloned and sequenced resulting in 87 different sequences. Amongst the 19 e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 29 publications
2
12
0
Order By: Relevance
“…The greater ability of wild type promoter genotypes to express hsp70.1 than the deletion mutant genotypes, as observed in our study, may partially explain the better milk production traits of wild type genotypes. These findings indirectly agree with Schwerin et al (2003a), who reported the association of the same SNP within hsp70 promoter to the shorter productive life. Previous studies highlighted the role of polymorphism within hsp70 promoter region to the reproductive parameters including pregnancy rate, calf weaning weights and fertility in dairy cattle (Bank et al, 2007;Rosenkrans et al, 2010;Starkey et al, 2007).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The greater ability of wild type promoter genotypes to express hsp70.1 than the deletion mutant genotypes, as observed in our study, may partially explain the better milk production traits of wild type genotypes. These findings indirectly agree with Schwerin et al (2003a), who reported the association of the same SNP within hsp70 promoter to the shorter productive life. Previous studies highlighted the role of polymorphism within hsp70 promoter region to the reproductive parameters including pregnancy rate, calf weaning weights and fertility in dairy cattle (Bank et al, 2007;Rosenkrans et al, 2010;Starkey et al, 2007).…”
Section: Discussionsupporting
confidence: 92%
“…It was found that heterozygous cytosine deletion mutant genotypes (C−) form majority with the absence of homozygous cytosine deletion mutant genotypes (−−) in tested population. Previously the polymorphism at same position had reported the presence of all three genotypes in Holstein dairy cows (Basirico et al, 2011;Schwerin et al, 2003a). Since the present study involves a cross breed Frieswal (Holstein × Sahiwal) population, it supports the concept that the genotype and allele frequency of the specific SNP may not be repeatable in different populations of same breed or in different breeds.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…The POFUT1 (protein O-fucosyltransferase 1) gene plays a crucial role in Notch signaling, which regulates mammary stem cell function and luminal cell-fate commitment [44]. TFAP2C (transcription factor AP-2 gamma; activating enhancer binding protein 2 gamma) is involved in mammary development, differentiation, and oncogenesis playing a critical role in gene regulation in hormone responsive breast cancer [45], and AHCY (adenosylhomocysteinase) has been suggested as potentially involved in mastitis defense based on its disease-associated expression [46]. Another positional candidate gene for this core region is the GHRH (growth hormone-releasing hormone) gene.…”
Section: Discussionmentioning
confidence: 99%
“…3, 4, 9, 11, 18 and 27, which recommends them as candidate chromosomes for fine mapping. This was done by Brunner et al (2003) and Mömke et al (2005) for Chr. 18.…”
Section: Quantitative Trait Locimentioning
confidence: 99%